Respuesta :
First, distribute.
[tex]3y - 27 = 7y + 2[/tex]
Subtract the 3y from both sides.
[tex] - 27 = 4y + 2[/tex]
Subtract 2 from both sides.
[tex] - 29 = 4y[/tex]
To get the variable by itself, divide by 4.
[tex] - \frac{29}{4} = y[/tex]
Your answer is:
[tex]y = - \frac{29}{4} [/tex]
[tex]3y - 27 = 7y + 2[/tex]
Subtract the 3y from both sides.
[tex] - 27 = 4y + 2[/tex]
Subtract 2 from both sides.
[tex] - 29 = 4y[/tex]
To get the variable by itself, divide by 4.
[tex] - \frac{29}{4} = y[/tex]
Your answer is:
[tex]y = - \frac{29}{4} [/tex]
Step-by-step explanation:
I'm really really sorry if I'm wrong...
3(y-9)=5y+2
3y - 27 = 5y + 2
+ 27 + 27
3y = 5y + 29
-5y -5y
-2y = 29
-2 -2
y = -14.5